Prototype Design of InMed (Information Medicine) Application Using Goal-Directed Design (GDD) Method with Figma - Tri Sulistyorini; Muhammad Achsan Isa AL Anshori; Nelly Sofi; Dwi Widiastuti (Asosiasi Dosen Muda Indonesia, 2025)
In the world of health, a platform is needed to make it easier for a person to find information, especially related to drugs practically. To realize this, this research was carried out to produce an application called InMed (Information Medicine). This research aims to analyze, design, and evaluate matters related to telemedicine and make it easier for users to find information about medicines. The method used in this study is Goal Directed Design (GDD) which consists of several steps, namely Research, Modeling, Requirements, Framework, Refinement, Support. The results of the Likert Scale test of the InMed application prototype received a score of 92%.